Serum Protein Binding of the Aminoglycoside Antibiotics - Gordon, Ralph C. (Antimicrob Agents Chemother, 1972)
The binding of four aminoglycoside antibiotics by human serum was investigated under controlled conditions of physiological pH and temperature, by means of an ultrafiltration technique. No serum binding was demonstrable for gentamicin, tobramycin, or kanamycin, whereas streptomycin was 35% bound. Previous conflicting studies are discussed, and some of the pharmacological implications are considered.